A fully soft switched point-of-load converter for resource constraint drone applications - Qu, Yong (2022)
The power efficiency and weight of present point-of-load (POL) dc-dc converters for drone applications are often compromised because they suffer from large switching losses at continuous conduction mode for heavy loads and excessive hardware overheads at discontinuous conduction mode for light loads. This paper presents a boundary conduction mode (BCM) control scheme for POL converters embodying a single operation mode. This is achieved by means of a hysteresis voltage controller to turn on/off the output power stage when necessary. The proposed BCM control scheme achieves high power efficiency (≥91.2%) over a wide load range (5 mA-1 A) by means of fully soft switching. Specifically, a hysteretic current controller is proposed to realize ZCS, and an adaptive dead time controller is proposed to realize ZVS. Further, the proposed BCM control scheme requires a small output inductor (0.82 μH) by means of designing the customizable peak inductor current. To verify the proposed BCM control scheme, we realize a BCM-based POL converter that features an input voltage range of 5-16 V, output voltage range of 2.5-8 V, switching frequency of 1.5 MHz, peak power efficiency of 96.8%, and ≤35 mV output voltage undershoot/overshoot for 1-A load step. When being benchmarked against state-of-The-Art counterparts, the proposed design features the lowest voltage undershoot/overshoot, the highest switching frequency, ∼5.7× smaller inductor, and ∼11% higher power efficiency at light loads.